2020
DOI: 10.1007/s40279-020-01310-y
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Sport-Related Injuries and Longer Term Impact in Retired Male Elite- and Amateur-Level Rugby Code Athletes and Non-contact Athletes: A Retrospective Study

Abstract: Background Rugby union and rugby league are popular team contact sports, but they bring a high risk of injury. Although previous studies have reported injury occurrence across one or several seasons, none have explored the total number of injuries sustained across an entire career. As the first to do so, the aim of this study was to report on cumulative injuries and their perceived long-term impact in retired rugby code athletes compared to athletes from non-contact sports. Methods One hundred and eighty-nin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 38 publications
0
41
2
Order By: Relevance
“…Coaches perceived rugby players were at high risk of injury, agreeing with evidence that injuries can have detrimental effects on team performance, 30 an athlete's career 31 and their quality of life. 31 32 Coaches and players felt it was possible to prevent rugby injuries, identifying the positive effects rugby specific warm-ups can have on injury risk.…”
Section: Discussionmentioning
confidence: 81%
“…Coaches perceived rugby players were at high risk of injury, agreeing with evidence that injuries can have detrimental effects on team performance, 30 an athlete's career 31 and their quality of life. 31 32 Coaches and players felt it was possible to prevent rugby injuries, identifying the positive effects rugby specific warm-ups can have on injury risk.…”
Section: Discussionmentioning
confidence: 81%
“…Coaches in both groups demonstrated awareness that rugby injuries can have a detrimental effect on a player’s career [ 38 ], quality of life [ 38 , 39 ], and team performance [ 40 ]. Coaches displayed knowledge that completing a rugby-specific warm-up can reduce injury risk [ 2 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…These activities, if repeated, could be detrimental to the joint, as a study calculated the risk of developing localized OA to be twice as likely in individuals with occupations demanding repetitive physical activities compared to the average population (110). Moreover, although recreational sports activities are known to lower the occurrence of OA, elite athletes participating in competitive sports are extremely prone to OA, as incorrect execution of movements may disturb joint stabilization (111)(112)(113)(114). In a systematic review including over 8,400 subjects, it was concluded that soccer, weightlifting, and wrestling were the sports with the highest prevalence of knee OA (112).…”
Section: General Characteristics Of Oamentioning
confidence: 99%
“…In a systematic review including over 8,400 subjects, it was concluded that soccer, weightlifting, and wrestling were the sports with the highest prevalence of knee OA ( 112 ). Furthermore, it has been reported that OA prevalence rates in contact sports, such as rugby, are twice as high as those in non-contact sports ( 113 ).…”
Section: Applications Of Msc Therapies In Oamentioning
confidence: 99%